Science, Linguistique, Littérature : trois disciplines, deux discours, une culture - Sandrine SORLIN (E-REA)
This paper aims at considering the methodological and epistemological boundaries separating three academic disciplines. Underlain by a discourse that is proper to the economy of their discipline, literature and science regard each other as two opposite cultures. Yet each tackles its object of study through a culturally-determined paradigm. The simultaneous birth of chaos theory in science and postmodern aestheticism in literature in the 70s for instance can only be accounted for if we think of them as belonging to the same culture, which, at some point, brought about a change in paradigm that informed all disciplines. Linguistics underwent the same process. Yet the question of its boundaries remains. We will see to what extent linguistics can be seen as cross-disciplinary, in its study of the rhetoric of both literary and scientific textuality.